2022
DOI: 10.1155/2022/2214411
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect of Nicorandil Combined with Aspirin in the Treatment of Myocardial Ischemia

Abstract: Objective. To investigate the clinical effect of nicorandil combined with aspirin in the treatment of myocardial ischemia. Methods. A total of 104 patients with myocardial ischemia were admitted to our hospital from June 2019 to August 2020. These patients were selected as the research objects and randomly divided into two groups: the control group and the observation group. The control group was given asilin, and the observation group was given nicorandil tablets based on the control group. Both groups were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(12 reference statements)
0
1
0
1
Order By: Relevance
“…Болюсне інтракоронарне введення нікорандилу пацієнтам з ІХС під час ЧКВ знижує активність системного запалення та оксидативного стресу, спричинену інтервенційним втручанням [14]. Комбінація нікорандилу з ацетилсаліциловою кислотою сприяє зменшенню вираженості ішемії міокарда у хворих на ІХС та супроводжується вірогідним (р<0,05) зростанням показників фракції викиду (ФВ) ЛШ, пікової швидкості раннього/пізнього діастолічного кровотоку (E/A), швидшим зниженням сегмента ST порівняно з контролем [15]. яскравим прикладом сприятливого впливу нікорандилу на коронарну мікроциркуляцію є результати нещодавно опуб лікованого багатоцентрового проспективного подвійного сліпого РКД CHANGE, в якому вивчали здатність нікорандилу впливати на розмір ІМ на тлі проведення ЧКВ [16].…”
Section: лікарю-практику | кардіологіяunclassified
“…Болюсне інтракоронарне введення нікорандилу пацієнтам з ІХС під час ЧКВ знижує активність системного запалення та оксидативного стресу, спричинену інтервенційним втручанням [14]. Комбінація нікорандилу з ацетилсаліциловою кислотою сприяє зменшенню вираженості ішемії міокарда у хворих на ІХС та супроводжується вірогідним (р<0,05) зростанням показників фракції викиду (ФВ) ЛШ, пікової швидкості раннього/пізнього діастолічного кровотоку (E/A), швидшим зниженням сегмента ST порівняно з контролем [15]. яскравим прикладом сприятливого впливу нікорандилу на коронарну мікроциркуляцію є результати нещодавно опуб лікованого багатоцентрового проспективного подвійного сліпого РКД CHANGE, в якому вивчали здатність нікорандилу впливати на розмір ІМ на тлі проведення ЧКВ [16].…”
Section: лікарю-практику | кардіологіяunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%